One Kick : - Cain, Chelsea (Simon & Schuster, 2014)
Kick Lannigan, abducted at age six, goes into a tailspin when a second Amber Alert in a month signals the disappearance of a child in the Portland area.That's when the enigmatic Bishop approaches her with a proposition. He made a fortune as a weapons dealer and now wants to make good by using his resources to rescue abducted children. And he is convinced Kick's experiences and expertise can be mined to help rescue the abductees. Little does Kick know the case will lead directly into her terrifying past.